Penggunaan Media Poster terhadap Kemampuan Literasi Numerasi Siswa Kelas V SD - Lestari, Dirga Ayu; Adilah, Nida; Hanifa, Millata; Ramadhan, Putri Utami; Fatkha, Magfirotul (el-Ibtidaiy:Journal of Primary Education, 2026)
This research is motivated by the low numeracy literacy skills of elementary school students, especially in connecting mathematical concepts to real life. Numeracy literacy is not just the ability to count, but the ability to apply the concept of numbers and symbols in everyday life. This article aims to analyze how poster media can be used as a learning instrument to improve the numeracy literacy of fifth-grade elementary school students. Through a literature review and descriptive qualitative analysis, the results of the study indicate that the use of attractive and informative poster media can visualize abstract mathematical concepts into more concrete ones, thereby increasing students' understanding and learning motivation. In addition, it was found that data and concept visualization in posters helped students reach the concrete operational stage better. As a result, there was an increase in data interpretation and contextual problem-solving skills